Chosen endocrinopathies in menopause – practical guidelines in diagnostics - Matuszek, Beata; Nowakowski, Andrzej; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
The paper presents practical guidelines in diagnosing the most frequent endocrinopathies in menopausal women. The frequency of thyroid disorders and type 2 diabetes rises with age and the hormones in the perimenopausal period create favourable conditions for the development of such endocrinopathies. Clinical picture, often mildly symptomatic, may resemble menopausal symptoms and their variety may mask the clinical picture of different cases of endocrinopathy, which makes the right diagnosis difficult to establish and causes medical problems that require interdisciplinary cooperation of many different specialists. The question of diagnostic screening tests still seems to be an unresolved issue. Some authors opt for routine thyroid diagnostics, while others recommend only detailed case finding with the assessment of risks factors in the post-menopausal period. The authors of this paper suggest that every perimenopausal woman should undergo thyroid tests and the presence of goitre should be a recommendation for detailed thyroid diagnostics including imaging. Taking into consideration natural development of type 2 diabetes together with a multidirectional character of pathogenic disorders induced by menopause, it seems that an oral glucose tolerance test (OGTT) rather than a fasting glucose test should serve as a primary diagnostic parameter.